Biotransformation of Naringenin by Bacillus amyloliquefaciens Into Three Naringenin Derivatives - Koirala, Manoj; Lee, Young Kee; Kim, Min Seon; Chung, You Chul; Park, Jin-Soo; Kim, Seung-Young (SAGE PUBLICATIONS INC, 2019)
In this study, a whole-cell biotransformation by Bacillus amyloliquefaciens Korean Collection for Type Culture 13588 was carried out to acquire naringenin derivatives. High-performance liquid chromatography analysis of the reaction metabolites showed the presence of 3 different products. The structure of the metabolites was confirmed through high-resolution quadrupole-time-of-flight electrospray-ionization mass spectrometry and nuclear magnetic resonance analysis. The result revealed that B. amyloliquefaciens catalyzes naringenin into 3 derivatives, naringenin 7-O-phosphate, naringenin 7-O-glucoside (prunin), and 6''-O-succinylprunin. To our knowledge, this is the first report of the production of 3 different derivatives when naringenin was used as a substrate. Furthermore, our study also revealed that the product naringenin 7-O-phosphate has approximately 45-fold higher water solubility than that of naringenin. Our finding suggests that biotransformation might solve the low bioavailability of flavonoids.
Keywords: ANTIBACTERIAL ACTIVITY; BIOLOGICAL-PROPERTIES; FLAVONOID NARINGENIN; WATER-SOLUBILITY